Effects of Exercise and Pomegranate-Black Carrot Juice Interventions on Mineral Metabolism and Fatty Acids - Bozbay, Kenan; Cinar, Vedat; Akbulut, Taner; Aydemir, Isa; Yasul, Yavuz; Aytac, Kursat Yusuf; Migliaccio, Gian Mario (Mdpi, 2024)
In this study, the effects of exercise applied to sedentary individuals and the use of pomegranate-black carrot juice on minerals, fatty acids and some biochemical parameters were examined. Twenty healthy sedentary men participated in this study. This research consisted of three stages. Blood samples were taken from the participants before this study (Baseline), after the participants exercised (60 min/day) for 10 days (Exerciseonly), after the participants were given pomegranate-black carrot juice mixture (100 mL/100 mL) along with exercise (60 min/day) for 10 days (Exercise+supp). While AST and ALT levels increased in the Exerciseonly phase, they showed a relative decrease in the Exercise+supp phase. It was determined that Mg level in the Exerciseonly phase decreased compared to the Baseline and the Exercise+supp phase. It was determined that the Zn level in the Exercise+supp phase increased compared to the Zn level in the Exerciseonly phase. It was determined that 6:0, 12:0 and 14:0 fatty acid levels increased in the Exerciseonly phase compared to the Baseline. A decrease was detected in the Exerciseonly phase compared to the Baseline 18:2n6c, 18:3n6 and 18:3n3 fatty acid levels. It can be said that exercise and the use of pomegranate-black carrot juice mixture in sedentary individuals have supportive and corrective effects on serum mineral, fatty acids and some biochemical parameters.
Keywords: exercise; pomegranate-black carrot juice; minerals; lipid metabolism